Investigation of relationship between inhalation injury assessment and prognosis in burn patients - Yang, Hyeong Tae (The Korean Surgical Society, 2011)
PURPOSE: Inhalation injury is one of the most severe morbidity and mortality factors in burn patients. The purpose of this study is to analyze the impact of inhalation injury to the prognosis of burn patients and to investigate the relationship between the inhalation injury assessment and the prognosis of patients. METHODS: Bronchoscopy was performed in 170 patients who had the suspicion of inhalation injury and the patients were reviewed retrospectively from January 2008 to December 2009. Mortality was compared between the factors of brochoscopic findings, age, total body surface area (TBSA) burned, carboxyhemoglobin (COHb) level, PaO(2)/FiO(2) (P/F) ratio. RESULTS: Of 170 patients, 28 patients had no inhalation bronchoscopic finding. 109 patients had mild inhalation, 31 patients had moderate inhalation, only 2 patients had severe inhalation findings. The patients of moderate and severe inhalation findings had higher mortality (48.5%) than mild inhalation patients (31.1%). The larger total burnsurface area in inhalation patients, the greater the mortality. When compared to total admitted burn patients during the same period, inhalation patients showed higher mortality in the patients between 10 to 40% total burn surface area. Inhalation patients whose P/F ratio was below 300 showed higher mortality than above 300. But inhalation patients whose COHb level was below 1.5 had no difference in mortality with patients above 1.5. The COHb level and P/F ratio was the statistically different factors between inhalation patients and non-inhalation group in the mortality. CONCLUSION: Bronchoscopic findings, age, TBSA burned, P/F ratio were related with mortality in inhalation patients. When the international standardization of bronchoscopic classification developed, it can be possible to assess the inhalation patients more objectively and that will lead to the advancement in inhalation treatment and research.